THE CORRELATION OF PARENTS ATTENTION, INTELLIGENCE QUOTIENT, AND STUDENT INTEREST TO MATHEMATICS OUTCOMES ON THE SEVENTH GRADE STUDENTS OF SMP - Derina Aisyah Santi Dewi; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2019)
The poor student's outcome correlates with some factors. They are parent's attention, Intelligence Quotient (IQ), and student’s interest. This research is aimed at the positive and significant correlation of parent's attention, intelligence quotient, and student’s interest to the mathematic outcome on the seventh-grade student of Muhammadiyah Junior High School (SMP Muhammadiyah) Pleret Bantul in the second semester academic year 2016/2017. This research population is all the seventh-grade students of SMP Muhammadiyah Pleret Bantul in the second semester academic year 2016/2017. It consists of six classes. Thirty-two students of VII B students were chosen to be the sample, and it uses random sampling. The data were collected by questionnaire, documentation, and test method. The questionnaire is used to collect a parent's attention and student’s interest data. The test is used to collect the student's outcome. The research instrument test uses a validity test, reliability test, and discrimination test. The prerequisite analysis test consists of normality tests, linearity tests, and independence tests. The data analysis to test the hypotheses use product-moment correlation analysis and double linear regression analysis. The results show a positive and significant correlation of parent's attention, intelligence quotient, and student’s interest in mathematics outcome. The double correlation coefficient (R) is 0,649, and the determination coefficient (R2) is 0,422. Linear regression equation . The relative contribution X1 is 70,958% , X2 is 26,950% and X3 is 39,409% and effective contribution , EC and